The Very First Modification of Pleuromutilin and Lefamulin by Photoinitiated Radical Addition Reactions-Synthesis and Antibacterial Studies - Son Thai Le; Dávid Páll; Erzsébet Rőth; Tuyen Tran; Nóra Debreczeni; Miklós Bege; Ilona Bereczki; Eszter Ostorházi; Márton Milánkovits; Pál Herczegh; Anikó Borbás; Magdolna Csávás (MDPI AG, 2021)
Pleuromutilin is a fungal diterpene natural product with antimicrobial properties, semisynthetic derivatives of which are used in veterinary and human medicine. The development of bacterial resistance to pleuromutilins is known to be very slow, which makes the tricyclic diterpene skeleton of pleuromutilin a very attractive starting structure for the development of new antibiotic derivatives that are unlikely to induce resistance. Here, we report the very first synthetic modifications of pleuromutilin and lefamulin at alkene position C19-C20, by two different photoinduced addition reactions, the radical thiol-ene coupling reaction, and the atom transfer radical additions (ATRAs) of perfluoroalkyl iodides. Pleuromutilin were modified with the addition of several alkyl- and aryl-thiols, thiol-containing amino acids and nucleoside and carbohydrate thiols, as well as perfluoroalkylated side chains. The antibacterial properties of the novel semisynthetic pleuromutilin derivatives were investigated on a panel of bacterial strains, including susceptible and multiresistant pathogens and normal flora members. We have identified some novel semisynthetic pleuromutilin and lefamulin derivatives with promising antimicrobial properties.